Ариус Дея—Arius dayi sp. n. (Cypriniformes, Ariidae) из Аравийского моря - Дмитренко, Е.М. (Вестник зоологии, 1974)
Arius dayi sp. n. belonging to the Arridae family is described. The differences from the closely related species A. thalassimus (Günther, 1864) are indicated.